Swimming under elevated hydrostatic pressure increases glycolytic activity in gas gland cells of the European eel - Schneebauer, Gabriel; Lindemann, Constantin; Drechsel, Victoria; Marohn, Lasse; Wysujack, Klaus; Santidrian, Elena; Dirks, Ronald Petronella Hubertus; Hanel, Reinhold; Pelster, Bernd (PLOS ONE, 2020)
In spite of many decades of research, the spawning migration of the European eel Anguilla anguilla from the European coast to the Sargasso Sea remains a mystery. In particular, the role of the swimbladder as a buoyancy regulating structure is not yet understood. In this study, we exercised silver eels in a swim tunnel under elevated hydrostatic pressure. The transcriptome of gas gland tissue of these exercised eels was then compared to the known transcriptome of not exercised (control) silver eel gas gland cells. Due to the high infection rate of the eel population with the swimbladder parasite Anguillicola crassus, the comparison also included an exercised group of silver eels with a heavily damaged swimbladder, and we compared the previously published transcriptome of not exercised silver eels with a highly damaged swimbladder with the exercised group of silver eels with a heavily damaged swimbladder. The comparisons of unexercised (control) silver eels with exercised silver eels with functional swimbladder (EF), as well as with exercised silver eels with damaged swimbladder (ED), both showed a significant elevation in transcripts related to glycolytic enzymes. This could also be observed within the comparison of unexercised silver eels with a highly infected swimbladder with exercised eels with a damaged swimbladder (DED). In contrast to EF, in ED a significant elevation in transcript numbers of mitochondrial NADH dehydrogenase was observed. While in EF the transcriptional changes suggested that acid production and secretion was enhanced, in ED these changes appeared to be related to thickened tissue and thus elevated diffusion distances. The remarkable number of differentially expressed transcripts coding for proteins connected to cAMP-dependent signaling pathways indicated that metabolic control in gas gland cells includes cAMP-dependent pathways. In contrast to ED, in EF significant transcriptional changes could be related to the reconstruction of the extracellular matrix, while in ED tissue repair and ...